A review of Plateros Bourgeois, 1879 (Coleoptera: Lycidae) from southeastern China, with descriptions of six new species from the Nanling Mountains - Fang, Chen; Yang, Yu-Xia; Yang, Xing-Ke; Liu, Hao-Yu (Zootaxa, 2024)
We review the species of the lycid genus Plateros Bourgeois, 1879 from Southeast China in this study. Six new species are described, including P. flavihumeralis sp. nov., P. incurvusimimus sp. nov., P. dinghuensis sp. nov., P. gracilis sp. nov., P. nanlingensis sp. nov., and P. nigripennis sp. nov. P. laocaensis Kazantsev, 2011 is recorded to China for the first time. Five previously known species, including P. chinensis Waterhouse, 1879, P. planatus planatus Waterhouse, 1879, P. propinquus (Waterhouse, 1879), P. incurvus (Bocáková, 1997) and P. laocaensis are illustrated with macrophotographs of habitus and aedeagi to make comparison with new species. In addition, a distribution map and a key to species of Plateros from Southeast China are provided.